The quantized transformation in Deng's grey relational grade. Issue 3 (7th November 2016) - Wen, Kunli
Abstract : Purpose: Until now, many different varieties of grey relational grade methods had been proposed, and there are also many relevant publications, which include ordinal grey relational grade and cardinal grey relational grade. However, the most original and important formula is Deng's grey relational grade. After careful study it was found that although it is an ordinal form of grey relational grade, a rational mathematics model can be used to transfer it from ordinal into cardinal. It not only can enhance the essential of Deng's grey relational grade, but also can let Deng's grey relational grade be used more widely. The paper aims to discuss these issue. Design/methodology/approach: The paper uses fuzzy set theory to get the rational value of distinguish coefficient in Deng's grey relational grade, then uses grey entropy method to decide the rational weighting for the analysis sequences in Deng's grey relational grade. Findings: Through the mathematics derivation, it indeed can transfer the Deng's grey relational grade from ordinal form into cardinal form. Practical implications: The paper has deeply enhanced the essential of Deng's grey relational grade, and made Deng's grey relational grade more available and more usable in grey system theory. Originality/value: The paper has transferred the Deng's grey relational grade from ordinal into cardinal, it can let Deng's grey relational grade be used in a wider area.